Pendeteksian Fraud Dalam Laporan Keuangan dengan Cash Flow Shenanigans pada Perusahaan BUMN yang Terdaftar di BEI Periode 2018-2022 - Pricylia, Dhea Aristy; Budiantara, Martinus (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Indonesia is one of the developing countries where the phenomenon of fraud is not unfamiliar to the public. Types of fraud that occur in Indonesia include financial statement fraud, misappropriation of state assets/wealth, and corruption. Therefore, it is essential to address financial statement fraud. This research aims to prove whether cash flow shenanigans have an impact on detecting fraud in financial statements. The results of the study indicate that days sales outstanding (DSO) significantly influences the detection of fraud in financial statements. Delaying payment of obligations (DPO) does not have a significant impact on detecting fraud in financial statements. Reducing inventory purchases (DSI) significantly influences the detection of fraud in financial statements. Net income (CFNI) significantly affects the detection of fraud in financial statements. Keywords : Cash Flow Shenanigans, Fraud, Financial Reports